PARENT'S PERSPECTIVE ON CHILDREN EDUCATION AT HANDIL SOHOR VILLAGE KOTAWARINGIN TIMUR - Surawan Surawan; Rika Siswanti (International Conference on Social and Islamic Studies, 2021)
The results showed that: 1. Parents' views on children's education include: a.Understanding, most of the subject said that education for children is important. The childreneducation should be continued to the higher level if the family has good economy. b. Theattitude, the attitude of parents’ care to their children's education is quite good, this can beproven from the existence of children's educational facilities which are always attempted bytheir parents. c. Responses, parents’ response to the children's education are generally good,because parents often give their children an advice regarding to how important education forthe future. 2. Parents’ duty and responsibility for children's education is sufficient. It can beseen from the parents who have not given faith development for their children. Few parents domoral education. In the intellectual development of children, it seems that the parents are stillnot optimal. It is proven by by the children who drop out of school. Whereas in the socialdevelopment, parents only give their advice to their children. 3. Factors which influenceparents on children's education are: a. lack of parental knowledge and understanding ofeducation. b. Lack of parental awareness of the importance of education in a family. c.Economic pressure for family needs.